(untitled) (International Journal of Engineering and Computer Science, 2016)
A lines of advances in organic memory technology is demonstrated that enable an entirely new low-cost memory technology. Inventors incorporate these advances with the one of the most flexible material PLASTIC. This novel memory technology can be utilized in a 3D onetime-programmable storage array. Without the prohibitive costs of silicon processing, this memory is able of setting cost points several orders of magnitude lower than their inorganic counterparts. They have also progressively integrated this technology onto flexible plastic substrates. Combined with stacking, these vertical memory elements can create read only memory densities denser than many inorganic memories, at a fraction of the cost. A conducting plastic has the potential to put into a mega bit of data in a millimetre-square device-10 times denser than current magnetic memories. This system is cheapand fast, but cannot be rewritten, so would only be suitable for permanent storage. The system sandwiches a blob of a conducting polymer called PEDOT and a silicon diode between perpendicular connection. The key to the new technology was discovered by passing high current through PEDOT (Polyethylenedioxythiophene) which converts it into an insulator, rather like blowing a fuse .The polymer hastwo possible states conductor and insulator, that form the one and zero, necessary to put into digital data